The factors that motivate residential property investments in Klang Valley / Cheah Chee Wei - Cheah, Chee Wei (2013)
Investment in residential property has long been recognized as an important component in an individual’s portfolio of investment. Malaysia’s residential property price had seen the fastest surge in price for the last two years whereby property prices in Malaysia particularly in Klang valley had risen between 20 to 80 per cent. The sheer magnitude of increase in residential property prices has compelled individual property investors to commit a substantial amount of their funds to purchase residential property leaving little capital for other kinds of investment. The purpose of this research is to investigate the factors that influence and motivate individuals to invest in property in the Klang Valley. This study will attempt to understand the factors that motivate individual’s investment decision and as to why property investment is preferred as a wealth creation tool compared to other forms of investment products. This study also attempts to investigate whether or not investor’s gender and property features have significant influence on investor’s property investment decision.